The application of ERAS in pilonidal sinus: comparison of postoperative recovery between primary suture and Limberg flap procedure in a multicenter prospective randomized trial - Lu, Wei; Huang, Shujuan; Ye, Hui; Xiang, Shang; Zeng, Xiangsheng (Frontiers in Surgery, 2024)
Purpose We evaluated the clinical effect of utilizing a Limberg rhomboid flap graft in conjunction with Enhanced Recovery After Surgery (ERAS) protocols for the management of pilonidal sinus in the sacrococcygeal region to demonstrate the feasibility of applying ERAS to the treatment of pilonidal sinus. Methods Between January 2010 and August 2018, prospective data analysis was undertaken on 109 patients who received surgical treatment for pilonidal sinus in the sacrococcygeal region at the Department of Colorectal and Anal Surgery, Jingzhou Hospital affiliated to Yangtze University, and Taizhou Traditional Chinese Medicine Hospital. The patients were randomly separated into two groups based onoperation technique: the control group (pilonidal sinus resection with primary suture) and the observation group (pilonidal sinus resection with Limberg flap graft). Some patients in the above two groups received ERAS after surgery, which included early feeding and early ambulation, etc. Therefore, we further subdivided each group into group A (without ERAS) and group B (with ERAS) according to whether they received ERAS. Comparative analysis was conducted to assess differences in pertinent data before and after surgery across the respective groups. Results The length of postoperative hospitalization was shorter and wound dehiscence was more common in control group B than in control group A. Observation group B exhibited significantly shorter wound recovery periods and postoperative hospital stays compared to observation group A. The hospitalization duration and wound healing time in observation group B were notably shorter than those observed in control group B, but the operation time was longer and scar acceptance was lower. The VAS score, infection rate, wound dehiscence rate, subcutaneous hematoma rate and 5-year recurrence rate in observation group B were lower than those in control group B, but the rate of flap ischemia or necrosis was higher. Conclusion The combination of ERAS with pilonidal sinus resection using Limberg flap graft demonstrated a reduction in infection rates, wound dehiscence, subcutaneous hematoma occurrence, and recurrence rates, along with alleviation of postoperative pain and acceleration of healing time. Comparatively, this approach offers superior advantages over pilonidal sinus resection with primary suture in the management of sacrococcygeal pilonidal sinus.